The Frameless Copper IUD (GyneFix) and the TCu380A IUD : Results of an 8-year Multicenter Randomized Comparative Trial - Meirik, O. (2012)
BACKGROUND: Clinical performance of the frameless copper IUD (GyneFix), designed to reduce side effects related to the frame of conventional IUDs, and TCu380A was compared. STUDY DESIGN: Randomized Multicenter randomized comparative trial. Parous women requesting and eligible to use IUD were admitted in 21 centers in eight countries in 1989-1993 and followed-up for up to 8 years. RESULTS: Two thousand twenty-seven women were randomized to the frameless IUD and 2036 to TCu380A; 43 insertions of the frameless IUD failed and none for TCu380A. First-year expulsion rate of the frameless IUD was 5.3 (95% CI: 4.4-6.4) per 100 and 2.5 (95% CI: 1.9-3.3) for the TCu380A; second- through eighth-year expulsion rates were not different. First-year pregnancy rates for the frameless IUD and TCu380A were 1.3 (95% CI: 0.9-2.0) and 0.5 (95% CI: 0.3-0.9), respectively; second- through eighth-year cumulative pregnancy rates were 1.2 (95% CI: 0.7-1.9) and 2.5 (95% CI: 1.8-3.4), respectively. The 8-year cumulative rates of ectopic pregnancy and IUD removal for pain were lower for the frameless IUD than for TCu380A. Removals for other reasons were not different. CONCLUSIONS: The frameless IUD had more insertion failures, expulsions and pregnancies in the first year than TCu380A, but fewer pregnancies from the second through the eighth year, and by 8 years had fewer ectopic pregnancies and removals for pain.